Dissociated vertical deviation and its relationship with time and type of surgery in infantile esotropia. Issue 6 (27th May 2010) - Arslan, Umut; Atilla, Huban; Erkam, Necile
Abstract : Aim: To investigate the development of dissociated vertical deviation (DVD) in infantile esotropia and its relationship with the infant's age and the surgical intervention technique. Material and method: The medical records of the patients that were diagnosed with infantile esotropia and followed-up in the Strabismus Department of our clinic (Department of Ophthalmology, Ankara University Faculty of Medicine, Ankara, Turkey) were reviewed retrospectively. The patients' ages at the time of admission, risk factors, ophthalmological examinations before and after treatment, and treatment mode were recorded and compared. Results: DVD was found to develop in approximately one-half of the cases (47.9%) at an average age of 3.2 years (20 months–5.5 years) regardless of the type of treatment. DVD developed in 80.5% of cases that had no surgery and in 37.5% of cases who were surgically treated. On comparison according to age, DVD was seen in 24.1% of the cases that were treated between ages 6 months and 2 years and in 52% of the cases that were treated after age 2 years. The difference was found to be statistically significant (p<0.01). On comparison according to the surgical technique, DVD developed in 34.8% of the cases who had undergone bimedial rectus recession and in 38% of the cases with unilateral recession and resection. This difference was not statistically significant (p>0.05). Conclusions: In the treatment of infantile esotropia, early surgical intervention to obtain binocularity and prevent amblyopia is associated with a reduced incidence of the development of DVD. It is concluded that the incidence of the development DVD increases if surgery is not performed, if performed at a later age, or if additional muscle surgery is needed during follow-up due to undercorrection.